2011
DOI: 10.1038/aps.2011.90
|View full text |Cite
|
Sign up to set email alerts
|

Novel gastroretentive sustained-release tablet of tacrolimus based on self-microemulsifying mixture: in vitro evaluation and in vivo bioavailability test

Abstract: Aim: To develop a novel gastroretentive drug delivery system based on a self-microemulsifying (SME) lipid mixture for improving the oral absorption of the immunosuppressant tacrolimus. Methods: Liquid SME mixture, composed of Cremophor RH40 and monocaprylin glycerate, was blended with polyethylene oxide, chitosan, polyvinylpyrrolidone and mannitol, and then transformed into tablets via granulation, with ethanol as the wetting agent. The tablets were characterized in respect of swelling, bioadhesive and SME pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…colloidal silica and magnesium stearate and compression force on hardness and dissolution of controlled release tablet of coenzyme Q10. It was also found that the solid carriers and compression force were in optimum level [76]. Tacrolimus was developed as gastroretentive SR tablet by using polyethylene oxide, chitosan, poly(vinyl pyrollidone) and mannitol as solid carrier.…”
Section: Recent Advancements In Seddsmentioning
confidence: 99%
“…colloidal silica and magnesium stearate and compression force on hardness and dissolution of controlled release tablet of coenzyme Q10. It was also found that the solid carriers and compression force were in optimum level [76]. Tacrolimus was developed as gastroretentive SR tablet by using polyethylene oxide, chitosan, poly(vinyl pyrollidone) and mannitol as solid carrier.…”
Section: Recent Advancements In Seddsmentioning
confidence: 99%
“…Wang et al .,[32] developed a novel gastro-retentive drug delivery system based on a self-microemulsifying (SME) lipid mixture for improving the oral absorption of the immunosuppressant tacrolimus. Liquid SME mixture composed of Cremophor RH40 and monocaprylinglycerate, was blended with polyethylene oxide, chitosan, polyvinylpyrrolidone, and mannitol, and then transformed into tablets via granulation, with ethanol as the wetting agent.…”
Section: Tacrolimus Drug Delivery Systemsmentioning
confidence: 99%
“…Tacrolimus is also a drug of choice for atopic dermatitis in reducing the side effects related with topical corticosteroids. Tacrolimus is classified as a class II drug according to the biopharmaceutical classification system (12). Tacrolimus exhibits poor aqueous solubility, P-gp efflux, and extensive presystemic metabolism resulting in low bioavailability following oral administration (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%